A10.20 On the Origin of the Type I Interferon Activity in Rheumatoid Arthritis. (25th February 2013) - Jong, TD de; Vosslamber, S; Eloranta, ML; Rönnblom, L; Mantel, E; Gelderman, KA; von Blomberg, ME; Bultink, IE; Voskuyl, AE; Verweij, CL
Abstract : Background: A role for type I interferon (IFN) activity is suggested in the pathogenesis of autoimmune diseases, including systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). While the mechanism of induction of the IFN activity in SLE is rather known, this remains to be determined for RA. This study aims to characterise the source of IFN activity in RA serum. Methods: Healthy PBMCs were exposed to serum from RA (n = 18) or SLE (n = 25) patients. IFNα protein production was measured in an immunoassay after 20 h incubation with 5% patient serum. Samples were also co-cultured with apoptotic or necrotic cell material, as this has proven to enhance IFNα production by SLE serum. Moreover, expression of IFN response genes (IRGs), IFNα and IFNβ mRNA was determined by qPCR after 4 h and 8 h incubation with 25% patient serum. To study the involvement of new protein synthesis, part of the samples was co-cultured with 2 µg/ml cycloheximide. All cultures were performed with healthy donor serum (NHS) as a negative control. Results: As expected, SLE serum induces more IFNα protein production compared to NHS (p = 0.0006). This increases even further in the presence of dead cell material. RA serum does not show more IFNα protein inducing activity than NHS, although a small, nonsignificant increase was observed in the absence of dead cell material. With respect to IRG induction, both RA and SLE sera induced higher levels compared to NHS. SLE serum showed IRG induction at 4 h, which remained high after 8 h. The IRG induction at 8 h was not decreased by CHX treatment, indicating that it occurs independently of new protein synthesis, supporting a proposed direct effect by IFNα. RA serum induced IRG induction only after 8 h, which was inhibited upon CHX treatment, suggesting an indirect induction process. The IRG induction by RA serum was positively correlated with IFNβ mRNA induction at 4 h and 8 h (p = 0.0023 and p = 0.0130, respectively), but not with IFNα mRNA induction. Conclusions: Altogether, these results indicate different mechanisms underlying the induction of type I IFN activity between SLE and RA.